Home Alone: Widows' Well-Being and Time - Maja Adena; Daniel Hamermesh; Michał Myck; Monika Oczkowska (Journal of Happiness Studies, 2023)
Using data from the Survey of Health, Ageing and Retirement in Europe (SHARE, 2004–17) and time diaries from Poland (2013), the U.S. (2006–16), the U.K. (2014–15) and France (2009–10), we examine differences between widowed and partnered older women in well-being and its development in widowhood. Most importantly, our analysis accounts for time use, an aspect which has not been studied previously. We trace the evolution of well-being of women who become widowed by comparing them with their matched non-widowed `statistical twins' and examine the role of an exceptionally broad set of potential moderators of widowhood's impact on well-being. We confirm a dramatic decrease in mental health and life satisfaction after the loss of partner, followed by a slow partial recovery over a 5-year period. An extensive set of controls recorded prior to widowhood, including detailed family ties and social networks, provides little help in explaining the deterioration in well-being. Unique data from time-diaries kept by older women in several European countries and the U.S. tell us why: the key factor behind widows' reduced well-being is increased time spent alone.
Keywords: I31; I19; J14; 300; Widowhood; Well-being; Social networks; Time use